IMMUNOPATHOLOGICAL CHANGES IN NEPHROTIC SYNDROME IN CHILDREN WITH ATOPIC DERMATITIS - У. Н. Каримова (Web of Journals Publishing, 2023)
The main manifestation of the nephrotic form of glomerulonephritis is nephrotic syndrome (UA), which is characterized by proteinuria (more than 2.5 g/day or 50 mg/kg body weight), oliguria, edema, hypoproteinemia, hypoalbuminemia, hyperlipidemia, hypercoagulation and develops as the main manifestation of acute and chronic glomerulonephritis [11,13,21].